The Pembinaan tentang Apologetika Kristen dalam Menghadapi Isu-isu Kristologi di Gekesia Kota Manna Bengkulu Selatan - yosef, hery budi; Silaban, Guntur; Kansil, Dicky; Chandra, Iyan (PkM: Pistotites, 2024)
Abstract This research is based on the widespread issues heard around the church, both inside and outside the church, related to Christology. The issue is increasingly growing because of the strong influence of social media witnessed by the masses, in this case the churches, especially in the Gekesia neighborhood in the Manna city area, South Bengkulu. Thus, all churches in the Inter-Church Cooperation Agency in South Bengkulu took the initiative to hold regular coaching to clarify Christian issues. The material that is our guidance is that the Church must be ready to face and "fight" all these issues with accountability of faith, or what is called Christian Apologetics. This coaching uses a dialectical - responsive method, namely the presenter as the key speaker first explains the main material in a narrative and monologue, then continues with the audience's response, in this case the church or Christians who are "affected" by the theological issue. The results of the coaching obtained a generally responsive and enthusiastic response through the many coaching participants who asked questions to the event moderator, and provided impressions of their experience of discussing with the resource persons. The event will take place from September 28 to October 1, 2023. Coaching will be held on the second day, namely September 29 2023 at 09:00 – 12:00, and continued at 13:30 – 15:00. The method we use is dialectic - responsive with an emphasis on education, namely applying the Bible as the basis we use to respond to attacks from issues regarding Christology. Of course, the implementation is through a strategy of correct Apologetics towards this effort. We who conducted the education saw that the number of participants who took part was 88 participants, dominated by the adult age group, relatively aged 35 – 60 years. Nearly 86% of the total number of participants present was enthusiastic, this indicates enthusiasm that really met their doctrinal curiosity needs.